2014
DOI: 10.1186/1471-2334-14-352
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological characteristics of individuals resistant to M. tuberculosis infection in a longitudinal TB household contact study in Kampala, Uganda

Abstract: BackgroundDespite sustained exposure to a person with pulmonary tuberculosis (TB), some M. tuberculosis (Mtb) exposed individuals maintain a negative tuberculin skin test (TST). Our objective was to characterize these persistently negative TST (PTST-) individuals and compare them to TST converters (TSTC) and individuals who are TST positive at study enrollment.MethodsDuring a TB household contact study in Kampala, Uganda, PTST-, TSTC, and TST + individuals were identified. PTST- individuals maintained a negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 28 publications
3
74
1
Order By: Relevance
“…Neutrophils also participate through the transfer of granuleswhich contain antimicrobial agents that traffic to early endosomes containing mycobacteria -to macrophages and through the production of S100 proteins 9, 10 . In some individuals who remain tuberculin skin test-negative despite prolonged and repeated exposure to M. tuberculosis, these innate immune responses may be sufficient to prevent infection 11 . Further genetic studies of these resistant individuals may identify new HDT targets 12 .…”
Section: Immune Responses To M Tuberculosismentioning
confidence: 98%
“…Neutrophils also participate through the transfer of granuleswhich contain antimicrobial agents that traffic to early endosomes containing mycobacteria -to macrophages and through the production of S100 proteins 9, 10 . In some individuals who remain tuberculin skin test-negative despite prolonged and repeated exposure to M. tuberculosis, these innate immune responses may be sufficient to prevent infection 11 . Further genetic studies of these resistant individuals may identify new HDT targets 12 .…”
Section: Immune Responses To M Tuberculosismentioning
confidence: 98%
“…The risk of progression to active TB disease in LTBI child is influenced by the virulence of the mycobacteria, bacillary load, age and patient's immune response (Seddon et al 2013;Ma et al 2014). HIV co-infection is the strongest known risk factor for progression of LTBI to active TB disease (Lai et al 2016).…”
Section: Risk Factors Of Disease Progressionmentioning
confidence: 99%
“…Indeed, attempts were made to improve the reliability of diagnostic tool as well as to know the factors that contribute to false positive or false negative results. For instance, a prospective study by Ma et al (2014) among household contact of smear positive TB on standard TB regimen in Uganda found that 5-15 years old age group had tendency to have persistently negative TST (Ma et al 2014). Furthermore, Oberhelman et al (2015) compared the used of culture and/or microscopic evaluation against PCR method for bacteriological confirmation of TB.…”
Section: Biomarkers To Predict Disease Progressionmentioning
confidence: 99%
“…Some studies have been family-based, while others used a traditional case-control design. The advantage of family-based studies of TB is that exposure is more certain even if variable [34, 35]. …”
Section: Previous Genetic Studies Of Tbmentioning
confidence: 99%